A Demographic Paradox: How Public School Students in New Orleans Have Become More Racially Integrated and Isolated Since Hurricane Katrina. Issue 9 (December 2018) - Kotok, Stephen; Beabout, Brian; Nelson, Steven L.; Rivera, Luis E.
Following the tragedy of Hurricane Katrina, New Orleans public schools underwent a variety of changes including a mass influx of charter schools as well as a demographic shift in the racial composition of the district. Using school-level data from the Louisiana Department of Education, this study examines the extent that New Orleans public schools are more or less racially integrated, racially segregated, and concentrated by poverty almost a decade after Katrina. The study utilizes exposure indices, inferential statistics, and geospatial analysis to examine how levels of school integration and segregation have changed over time. Our findings indicate that though a greater share of New Orleans schools are considered racially diverse than prior to Katrina, a greater share of minority students are now attending dually segregated schools, where over 90% of students are classified as minority and are receiving free/reduced lunch.